Evaluating the Gender Gap in Academic Achievement: The Role of Household WASH Access in Indonesia - Puji Lestari; Ahmad Komarulzaman; Pipit Pitriyan (Jurnal Ekonomi Pembangunan, 2025)
This study investigates the association between access to improved water and sanitation (WASH) and the academic performance of students in Indonesia, as measured by national examination (UN/EBTANAS) scores in Mathematics, Indonesian, and English. Utilizing pooled cross-sectional data from the Indonesia Family Life Survey (IFLS) waves 1–5, the analysis employs Ordinary Least Squares (OLS) regressions incorporating gender interaction terms and a comprehensive suite of individual, household, and contextual control variables. The empirical results demonstrate that access to improved water and sanitation is positively and significantly associated with higher academic achievement. Notably, the association between improved water access and examination scores is significantly more pronounced for female students, particularly in Mathematics and English. In contrast, improved sanitation exhibits a positive but gender-neutral association across all subjects. The heightened benefits observed for female students may be attributed to a reduction in time burdens associated with domestic water collection and enhanced menstrual hygiene management, both of which serve to mitigate school absenteeism. These findings underscore the critical importance of integrating water and sanitation infrastructure improvements into broader education and gender-equity policies in Indonesia. This study contributes to the existing literature by providing robust, gender-disaggregated evidence of the impact of WASH infrastructure on standardized academic outcomes using longitudinal household survey data.